Optimizing Red Blood Cell Consumption Using Markov's Decision-Making Process (Case study: Blood Bank of Zanjan Province Blood Transfusion Center) - Mahdi Yousefi Nejad; Mehran Khayat Rasouli; Zohreh Khalilpour (مدیریت مهندسی و رایانش نرم)
In this research, a novel method is proposed to optimize the costs associated with the supply chain of short-lived blood products, which is different from other existing methods. According to the novelty of this approach and the lack of familiarity with its difficulties, a scaling is applied in order to reduce the size of problem space, which can lower the accuracy of the solution. On the other hand, with regard to the problem solving dimensions, the number of solution iterations would be limited. Ultimately, after solving the above problems, the collected data are entered into the formulation of Markov’s decision-making process and solved using the successive approximation approach. The solution of this approach helps the decision-maker to choose one of (LIFO-LIFO), (FIFO-FIFO), and (LIFO, FIFO) policies. By investigating different costs and comparing various (LIFO-LIFO), (FIFO-FIFO), and (LIFO, FIFO) policies, it can be concluded over iterations that policies (LIFO-LIFO) and (LIFO -FIFO) policies have better performances than the (FIFO-FIFO) policy, and will cost much less in the long run.